The Dynamics of Indonesian Democracy (2021-2024): A Nonparametric Comparative Analysis of Democracy Indices and Their Aspects - Pardomuan Robinson Sihombing (Fakultas Ekonomi dan Bisnis Islam, 2026)
Amidst the global discourse on democratic regression, the state of democracy in Indonesia post-reform continues to show complex dynamics. This study will conduct a longitudinal comparative analysis of the Indonesian Democracy Index (IDI) and its three components—Freedom, Equality, and Capacity of Democratic Institutions from 2021 to 2024 in 34 provinces. Given that the data is not normally distributed based on the Shapiro-Wilk test, the methodology used is the Friedman nonparametric test, followed by the Durbin-Conover post-hoc test for paired comparisons. The results show a statistically significant increase in the composite IDI score (χ2=15.8, p=0.001), the Equality aspect (χ2=21.5, p<0.001), and the Capacity of Democratic Institutions aspect (χ2=29.9, p<0.001) during the observation period. However, a crucial finding shows no statistically significant change in the Freedom aspect (χ2=6.53, p=0.089). This study argues that statistical improvements in several aspects likely reflect procedural and administrative progress driven by government policies. However, this progress can potentially obscure the reality of a more complex and sometimes contradictory substantive democracy, particularly in civil liberties and institutional integrity.